ISOLATION OF SOME BACTERIAL STRAINS FROM DIOXIN-CONTAMINATED SOIL IN A LUOI, THUA THIEN HUE - Sinh, Dương Đức Hoàng; Thi, Trần Vũ Ngọc; Thanh, Lê Thị Hà; Lan, Phạm Thị Ngọc; Lộc, Nguyễn Hoàng; Huy, Nguyễn Đức (Hue University Journal of Science: Natural Science, 2018)
This study presents the results of the isolation of some bacterial strains that are able to degrade dibenzofuran, a dioxin derivative, from the dioxin-contaminated soil in A Luoi district, Thua Thien Hue province. Soil samples were collected at 5 different sites of the old Aso airbase. Three bacteria strains were found to grow well on the basal minimal medium supplemented with dibenzofuran as a carbon source. The analysis of 16S rDNA sequences of the isolates showed that they were highly similar to Enterobacter cloacae (99%), Staphylococcus sp. (99%) and Achromobacter sp. (100%). Thus, they were named as Enterobacter cloacae DF3, Staphylococcus sp. DF5, and Achromobacter sp. DF6. The nucleotide sequence data were registered on the GenBank with accession numbers of MG774409, MG774408, and MG774410, respectively.